2017
DOI: 10.35808/ersj/724
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Antecedent and Consequence of Employee Engagement in Small and Medium-Sized Enterprises in Central Java, Indonesia

Abstract: Nowadays, employee is considered essential in an organization. The active role of the employee should be concerned by practitioners and academicians. This study aimed to investigate the antecedent and consequent variables of employee engagement.Distributive justice, absorptive capacity, and job design were believed as the antecedent factors influencing work engagement. Meanwhile, organizational citizenship behavior was believed as the consequent or output factor of employee engagement. The respondents were 134… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…Anitha (2014) determined that work environment and coworker relationship had a significant impact on employees' engagement among other variables which were leadership, training and career development, compensation programmes, policies and procedures and workplace wellbeing. Another study conducted by Handayani, Anggraeni, Andriyansah, Suharnomo and Rahardja (2017) in SMEs in Central Java, Indonesia found that distributive justice had a significant effect on employees' engagement among other variables; knowledge creation and work design.…”
Section: Employees' Engagementmentioning
confidence: 97%
“…Anitha (2014) determined that work environment and coworker relationship had a significant impact on employees' engagement among other variables which were leadership, training and career development, compensation programmes, policies and procedures and workplace wellbeing. Another study conducted by Handayani, Anggraeni, Andriyansah, Suharnomo and Rahardja (2017) in SMEs in Central Java, Indonesia found that distributive justice had a significant effect on employees' engagement among other variables; knowledge creation and work design.…”
Section: Employees' Engagementmentioning
confidence: 97%
“…Among the factors that are expected to lead to employee engagement is leadership style. Other attributes cited in previous study in the workplace are the study of Handayani et al (2017) asserting that employees display various levels of personal engagement or disengagement based on three types of attributes: (a) cognitive, (b) emotional, or (c) physical. The cognitive aspect is about employees' beliefs about an organization.…”
Section: Global Leadership Stylementioning
confidence: 99%
“…Sugandini et al, try to explain employee engagement in SMEs area in Yogyakarta, Indonesia, the result were employee engagement has proved to be a mediator between job satisfaction and reward to commitment and Leader Member Exchange (LMX) [2]. Handayani et al, used employee engagement as a mediator between distributive justice, knowledge creation and work design toward OCB, the result showed that distributive justice and knowledge creation has significance relationship to employee engagement, where employee engagement also significantly related with OCB [3]. Ariani analysed employee engagement as a mediator between supportive leadership toward OCB, the result showed that employee engagement was not supported as a mediator between supportive leadership toward OCB [4].…”
Section: Introductionmentioning
confidence: 99%